Effects of sources and levels of dietary supplementary manganese on growing yak’s in vitro rumen fermentation - Lu, Huizhen; Liu, Pengpeng; Liu, Shujie; Zhao, Xinsheng; Bai, Binqiang; Cheng, Jianbo; Zhang, Zijun; Sun, Cai; Hao, Lizhuang; Xue, Yanfeng (Frontiers in Veterinary Science, 2023)
Introduction Manganese (Mn) is an essential trace element for livestock, but little is known about the optimal Mn source and level for yak. Methods To improve yak’s feeding standards, a 48-h in vitro study was designed to examine the effect of supplementary Mn sources including Mn sulfate (MnSO4), Mn chloride (MnCl2), and Mn methionine (Met-Mn) at five Mn levels, namely 35 mg/kg, 40 mg/kg, 50 mg/kg, 60 mg/kg, and 70 mg/kg dry matter (includes Mn in substrates), on yak’s rumen fermentation. Results Results showed that Met-Mn groups showed higher acetate (p < 0.05), propionate, total volatile fatty acids (p < 0.05) levels, ammonia nitrogen concentration (p < 0.05), dry matter digestibility (DMD), and amylase activities (p < 0.05) compared to MnSO4 and MnCl2 groups. DMD (p < 0.05), amylase activities, and trypsin activities (p < 0.05) all increased firstly and then decreased with the increase of Mn level and reached high values at 40–50 mg/kg Mn levels. Cellulase activities showed high values (p < 0.05) at 50–70 mg/kg Mn levels. Microbial protein contents (p < 0.05) and lipase activities of Mn-Met groups were higher than those of MnSO4 and MnCl2 groups at 40–50 mg/kg Mn levels. Discussion Therefore, Mn-met was the best Mn source, and 40 to 50 mg/kg was the best Mn level for rumen fermentation of yaks.